Ð‘Ð¸Ð¾ÑÐ»ÐµÐºÑ‚Ñ€Ð¸Ñ‡ÐµÑÐºÐ°Ñ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ð¼Ð¾Ð·Ð³Ð° Ð¸ Ð¼Ñ‹ÑˆÑ† ÐºÑ€Ñ‹Ñ Ð² Ð¿Ñ€Ð¾Ñ†ÐµÑÑÐµ Ð²Ñ‹Ñ…Ð¾Ð´Ð° Ð¸Ð· Ð¸ÑÐºÑƒÑÑÑ‚Ð²ÐµÐ½Ð½Ð¾Ð³Ð¾ Ð³Ð¸Ð¿Ð¾Ð¼ÐµÑ‚Ð°Ð±Ð¾Ð»Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ñ - Shilo, A. V.; Lomako, V. V.; Ventskovskaya, E. A.; Babijchuk, G. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
In rats there was studied bioelectrical activity (BA) of brain and muscles during quitting from the state of artificial hypometabolic state, achieved with Anjus-Bakhmetâ€™ev-Giaja method (the method of â€œclosed vesselâ€). Just after the effect the depression of all frequency components of electroencephalogram (EEG) is observed, in some animals the EEG shows generalization of activity of heart and respiration. The recovery of brain BA occurs on the background of dominating of Î´-activity, in the process of self-warming the power and number of spectral components of EEG increase. Herewith at the stage of growing muscle activity the share of Î²-waves rises. The studied indices of BA approach the norm in 2 hrs after artificial hypometabolic state.